If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -8 = (-2) + v(-7) Combine like terms: 22 + -8 = 14 14 = (-2) + v(-7) 14 = -2 + v(-7) Reorder the terms for easier multiplication: 14 = -2 + -7v Solving 14 = -2 + -7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7v' to each side of the equation. 14 + 7v = -2 + -7v + 7v Combine like terms: -7v + 7v = 0 14 + 7v = -2 + 0 14 + 7v = -2 Add '-14' to each side of the equation. 14 + -14 + 7v = -2 + -14 Combine like terms: 14 + -14 = 0 0 + 7v = -2 + -14 7v = -2 + -14 Combine like terms: -2 + -14 = -16 7v = -16 Divide each side by '7'. v = -2.285714286 Simplifying v = -2.285714286
| Y=-3sen(2x)/x^2 | | 8(x+2)+8x=2(8x+6) | | 8n=108 | | 3.8+x=0.6 | | -1(x+4)= | | 6.37+4.2c=7.4c+8.95 | | 8x+3=-53 | | -8a+(-15a)= | | 2x+8(9x+6)=48 | | (6x^2+7x-9)-(8x^2-4x+7)= | | (45x^2+36x^3)= | | 4x-2x+5=21 | | k/2-9=30 | | C=7000-4B | | 4-4x=-4(x-1) | | (2x)3=54 | | -7x^2-9x=0 | | 5(-6+a)= | | k/2-7=15 | | (6g)(4z)=(3g)(t) | | -(x^2-x+1)=0 | | 8=1/2+3 | | X/5-2.5=3 | | -3y+12=-28 | | 6g*4z=3g*t | | p^2(3p-1)= | | -5n+4(1-n)=-8(n+7)+3n | | (-3)(7)+(-25)= | | 9x+5x-(4x+2)= | | 6g*4z=6g*t | | 3.14*81*5= | | 7x-17=87x+11 |